(untitled) (Journal of Nepal Geological Society, 2008)
The rapidly increasing population in the Kathmandu valley has demanded for the construction of multi-storeyed buildings. Such structures can be vulnerable to failures as they are constructed on soft fluvio-lacustrine sediments without detailed deformation analysis of their foundation. Hence, the Bir Hospital Trauma Centre is taken here as a case study for the deformation analysis. The settlement calculated by conventional test methods (e.g., oedometer test, compressibility index, etc.) are purely one dimensional and do not represent the actual value where lateral influence s are possible. For example, the settlement reckoned from conventional methods was 41.6 mm for the stratification below 4 m depth and 24 mm for the stratification below 8 m depth. On the other hand, using a finite element method, it was 42.5 mm for the stratification below 8 m depth.